2023
DOI: 10.3389/fimmu.2023.1125395
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue aging is regulated by an altered immune system

Abstract: Adipose tissue is a widely distributed organ that plays a critical role in age-related physiological dysfunctions as an important source of chronic sterile low-grade inflammation. Adipose tissue undergoes diverse changes during aging, including fat depot redistribution, brown and beige fat decrease, functional decline of adipose progenitor and stem cells, senescent cell accumulation, and immune cell dysregulation. Specifically, inflammaging is common in aged adipose tissue. Adipose tissue inflammaging reduces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 238 publications
0
9
0
Order By: Relevance
“…Alternatively, intrinsic sex differences in immune system have been demonstrated as well ( Chen et al, 2021a ; Singer et al, 2015 ) that are dependent on sex chromosome complement and/or Xist expression ( Syrett et al, 2018 ; Pyfrom et al, 2021 ), and RELMα may be regulated by these as well. Additionally, aging-mediated increase in inflammation (including of adipose tissue, recently reviewed in Zhang et al, 2023 ), may also occur via changes in RELMα levels. Our studies used young but developmentally mature mice (4–6 weeks old when placed on diet, 18 weeks old at sacrifice), and future work on aged mice would be needed to investigate aging-mediated inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, intrinsic sex differences in immune system have been demonstrated as well ( Chen et al, 2021a ; Singer et al, 2015 ) that are dependent on sex chromosome complement and/or Xist expression ( Syrett et al, 2018 ; Pyfrom et al, 2021 ), and RELMα may be regulated by these as well. Additionally, aging-mediated increase in inflammation (including of adipose tissue, recently reviewed in Zhang et al, 2023 ), may also occur via changes in RELMα levels. Our studies used young but developmentally mature mice (4–6 weeks old when placed on diet, 18 weeks old at sacrifice), and future work on aged mice would be needed to investigate aging-mediated inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammaging occurs in aged adipose tissue, where it contributes to adipocyte hypertrophy and dysfunction; there is also an increased infiltration of immune cells in adipose tissue and these immune cells secreted proinflammatory cytokines [ 51 ]. Animal studies showed that adipose-tissue derived TNF-α (AT-TNF) activity was elevated in older animals, while AT-TNF protein levels where higher in young animals, suggesting that they may secrete an inhibitor that reduces AT-TNF activity [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Jin and Bi[ 66 ], a microarray study shows that HBV significantly increases the expression of Bcl-2-like protein 11 in HBV-specific CD8+ T cells, pointing to a critical mechanism for CD8+ T cell depletion during CHB infection. Inhibitory receptors such as PD-1, CTLA-4, CD244 (2B4), Tim-3, and lymphocyte activation gene 3 are present on exhausted HBV-specific CD8+ T cells, and these receptors closely resemble the transcriptional patterns of CD8+ T cells[ 66 , 77 ].…”
Section: Possible Immunological Mechanisms Of Hbv Reactivationmentioning
confidence: 99%